การเปิดรับข่าวสาร ความรู้ และทัศนคติของข้าราชการไทยเกี่ยวกับการลงทุนของกองทุนบำเหน็จบำนาญข้าราชการ (กบข.) - อาภาพร เอกวัฒนากิจ (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The purpose of this research was to study the correlation among media exposure, knowledge and attitude of government officials toward the investment of Government Pension Fund (GPF). Questionnaires were used to collect the data from 600 samples. Frequency, Percentage, Mean, T-test, One-Way Analysis of Variance, Standard Deviation and Pearsonʼs Product Moment Correlation Coefficient were employed for the analysis of the data. SPSS for windows program was used for data processing. The results of the study were as follows: 1. Government officials were exposed to information about the investment of Government Pension Fund (GPF) at the low level. Their knowledge of the investment of GPF were at the moderate level while their attitudes toward the investment of GPF were neutral. 2. Sex and region of residence correlated with information exposure about the investment of GPF, but age, education and years of service did not correlate with information exposure about the investment of GPF. 3. Both mass and interpersonal media exposure did not correlate with knowledge of the investment of GPF. 4. Only exposure to specialized media about the investment of GPF positively correlated with knowledge of the investment of GPF. 5. Exposure to information about the investment of GPF did not correlate with attitude toward the investment of GPF. 6. Knowledge about the investment of GPF positively correlated with attitude toward the investment of GPF.